Hitotsubashi on knowledge management - Takeuchi, Hirotaka (John Wiley & Sons (Asia, 2004)
Knowledge Management (KM) is the art and science of utilizing knowledge as the most important resource towards gaining competitive advantage in today's business environment. Despite the huge and growing interest in KM, there has been no serious attempt to bridge theory and practice, the practices of East and West, the soft side (organizational capabilities) with the hard side (information technology), or the practices of large companies with start-ups. Until now. Written by the Dean of Hitotsubashi Business School in Tokyo, the world's leading centre of KM, and featuring contributions from thought leaders around the world, this book will provide a synthesis towards the emerging field of KM. It brings together the latest trends in the field and re-ignites the debate on the future form of knowledge management.